Semantic Web Untuk Pencarian Lembaga Pendidikan Provinsi Daerah Istimewa Yogyakarta - Daniel Alexander Octavianus Turang (Jurnal Mantik Penusa, 2017)
Educational Institution is an institution that is strategizes in generating and improving the quality of human resources in a country. Information and location search is needed in community organizations to determine the selection of the desired institute. In this study, knowledge of Institutions in Yogyakarta is stored in a web-based ontology model. Yogyakarta is famous as a city of students and a destination for studying. Schools consisting of formal educational institutions and non-formal institutions, formal education institutions consist of elementary school, junior high school, senior high school, university and so on, while non-formal education institutions consist of private Institute courses and the Institute for Training and Skills.This research aims to design the ontology of educational institutions province of Yogyakarta and search systems design. The results of this study is the development a search application using a search based on keywords and criteria. In search using keywords, users can conduct a search according the user's knowledge. While using a search criteria, users can perform a search with the criteria contained in the application with the help of an option to search. In addition, the application also has several features, such as the route to the location of existing educational institutions in Yogyakarta.